Axe in hand : a woodchopper's guide to blades, wood, and fire - Coenen, Nicole (Cool Springs Press, 2025)
"In Axe in Hand, lumberjack (and popular Instagram/TikTok star) Nicole Coenen teaches everything axes, woods, and fire for a new generation of outdoors people"--